Challenges to the Availability and Affordability of Essential Medicines in African Countries: A Scoping Review - Yenet A; Nibret G; Tegegne BA (Dove Medical Press, 2023)
Aderaw Yenet, Getinet Nibret, Bantayehu Addis Tegegne Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Bantayehu Addis Tegegne, Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia, Tel +251 9 13 32 62 85, Email bantayehuaddis.90@gmail.comIntroduction: The availability and affordability of safe, effective, accessible, and high-quality essential medicines is a critical benchmark for achieving the right to good health, and it is also one of the goals of the global health development agenda. To that end, it is critical to conduct rigorous studies to identify the major challenges confronting developing countries, particularly those in Africa.Objective: The purpose of this review was to identify the major challenges that Africans face in obtaining reasonably priced and readily available essential medicines.Methods: Generally the Boolean operators "AND" and "OR" were employed. Making progress also involves using duplicate checks, field definitions, and comparisons of articles and criteria. The analysis included all English-language papers published in any African country between 2005 and 2022, depending on the year of publication. The technique searches electronic databases for key phrases related to essential medication availability and affordability, such as PubMed, Web of Science, Scopus, Science Direct, Plos Medicine, and Google Scholar.Results: A total of 91 articles; by using search engines and handpicking including duplicates, were primarily searched. The electronic database search earned 78 articles while only eleven studies met the criteria for review and were reviewed of which 5 (50%) were from East African countries. Inadequate human resources, financial constraints, high cost of available medications on the market, poor inventory management, manual consumption forecasting, inefficiencies in drug registration, and trade-related aspects of intellectual property rights agreement regulations are all obstacles to the availability of essential medicines in African nations.Conclusion: This review revealed that in Africa, the availability and affordability of essential medicines face numerous challenges. The primary challenge, according to the review research, is a lack of adequate financing to pay for an appropriate set of essential medications, which account for a significant portion of household spending.Keywords: African countries, availability, affordability, essential medicines, challenges